Short Essay treatment of brucellosis with Tetracycline compound - Cuadra, Manuel (1959)
We have tried a short treatment of Brucellosis in a group of 22 febrile patients. Fourteen patients arrived in the course of the first acute attack of disease; none have received precious antibiotic theraphy; the remaining eight patient came in the course of febrile relapses and after having been treated with antibiotics (low or moderate doses, and during a relativity short time). All the patients were treated with 1 daily gram of Tetracicline or its derivatives (0.250 grams every 6 hours, during 5 days; 5 grams in all). If febrile relapses occurredm re-treatment with the same dosage was made. All the patients became afebrile within 1 and 7 days after institution of therapy, the most frequent being 4 days (37 febrile waves in the total of 22 patients). From the 22 patients 7 did not have febrile relapses, fourteen did and one could not be controlled. 19 patients have been observed for from 1 to 4 years; these patients, according to the number of relapses observed during that time, may be divided in three groups : 1.- Patients who recovered without having febrile relapses, 7 cases (null tendency to relapses, 7 cases (moderate tendency to relapses); 3.- Patients who were cured after having several febrile relapses, 4 cases (strong tendency to relapses). An old patient with marked tendency to relapses died (necropsy : endocardic lesions, brucella endocarditis?). In the patients with a tendency to febrile relapses who were treated with 5 grams of Tetracicline, the duration of the afebrile intervals (the one separating 2 febrile waves) was 6 days as a minimun and 285 days as a maximun, the most frequent interval ranging from 20 to 70 days. Two patients with a marked tendency to febrile relapses (on had 4 febrile waves and the other 7 in one year) were cured with periodical repetition of the 5-day short treatment (intermitent short treatment). Duration of the observations : 1 year and 8 months for one, and 3 years and 3 months for the other (last control: July 1958; the patient are healthy). The possibility of attaining a better chance of cure of Brucellosis by giving 5 short courses of theraphy with Tetracicline, at regular intercals, is suggested.